ANALISIS PENGARUH KARAKTERISTIK WILAYAH (KELURAHAN) TERHADAP BANYAKNYA KASUS DEMAM BERDARAH DENGUE (DBD) DI KOTA SEMARANG - Rahmawati, Rita; Kartono, Kartono; Sulistyo, Robertus Heri; Noranita, Betha; Sarwoko, Eko Adi; Wardaya, Asep Yoyo (MEDIA STATISTIKA, 2012)
DBD still become one of the major problems of public health in Indonesia because the death rate tended sufferers to increase from year to year. Incredible happening (KLB) of DBD which was initially occurring every five years, now it’s getting often happens. In the city of Semarang, during 2009 occurring 165 times KLB in urban village, 35 times KLB in the level of community health centers and 15 times KLB at the district level. Though the number of DBD cases in 2009 from 2008 was declining, but in this year also noted that the number of deaths resulting from DBD increased to 43 people from 18 people in 2008. This research aims to analyze the characteristics of the neighborhood (whose data is always updated by BPS via PODES) that affect the number of cases of DBD (whose data is always updated by DKK) in Semarang city, by creating the best regression models using stepwise technique. Regression model analysis of results obtained best is Y = 23.029 + 0.004 X1 – 0.074 X2 + 0.070X3, where Y is IR/10000 PDDK, that is the number of residents affected by DBD for each 10000 inhabitants, X1 is the number of residents aged 15-24 years, X2 is total area of land of rice fields and X3 is area of land for buildings and grounds around the page. Keywords: DBD, Characteristics of the Neighborhood, Regression, Stepwise